Assessment of the sea cucumber resource and fishery in the Bolinao-Anda reef system - Olavides, Ronald Dionnie Daposala; Edullantes, Christine Mae Asibal; Menez, Marie Antonette Juinio (Science Diliman: A Journal of Pure and Applied Sciences; Vol 22 No 2 (2010), 2011)
Fishery-independent and -dependent surveys were conducted to assess the status of the sea cucumber resource and fishery in Bolinao and Anda, Pangasinan. Thirty-five species of holothurians were recorded in 25 sampling stations within seagrass beds, coral reefs and mixed habitats. The estimated total population density of all aspidochirote sea cucumber species is 63 ind. ha -1 . The artisanal multi-species fishery is at present primarily based on Holothuria scabra , Stichopus horrens and Bohadschia marmorata although there are indications that other high-value species were fished to local extinction. Taken together, the small sizes (<20 cm body length) of the majority of aspidochirote sea cucumbers, their low population densities, and the continuous decrease in catches are clear signs of an overexploited fishery that will likely collapse without management intervention. Adaptive management strategies for Bolinao and Anda are recommended based on the findings of this survey.
Keywords: biodiversity; holothurians; resource assessment; resource management; sea cucumbers; trepang